Probing the non‐native states of Cytochrome c with resonance Raman spectroscopy: A tool for investigating the structure–function relationship. (23rd January 2018) - Milazzo, Lisa; Tognaccini, Lorenzo; Howes, Barry D.; Smulevich, Giulietta
Abstract: Cytochrome c (Cyt c) is a single polypeptide chain hemoprotein located in the mitochondrial intermembrane space. Under physiological conditions, His18 and Met80 are the fifth and sixth axial ligands, respectively, of the heme iron. Cyt c plays important roles in the cell because it acts as an electron carrier in the respiratory chain and as a reactive oxygen species scavenger. Moreover, direct interaction with cardiolipin, a phospholipid of the mitochondrial membrane, induces acquisition of peroxidase activity and subsequent release of Cyt c into the cytosol, where it acts as an apoptosis initiator. Cyt c has been extensively studied as a model protein to understand the general principles of protein folding, and it has been reported that the Met80 sixth ligand can be replaced by other internal or exogenous ligands depending on the pH or the presence of denaturing agents. The combination of ultraviolet–visible absorption and resonance Raman (RR) spectroscopy is a precious tool to identify the sixth heme iron ligand in the misligated forms. In particular, specific RR markers have been identified for each non‐native ligand. In this review, we illustrate the spectral variations and the corresponding RR marker bands observed for the different non‐native species. Furthermore, on the basis of these findings, we discuss the results obtained on the interaction of Cyt c with cardiolipin and the effect of mutating key residues in the Cyt c heme cavity, which has enhanced insight into protein unfolding and apoptosis. Abstract : Under physiological conditions, His18 and Met80 are the fifth and sixth axial ligands of the cytochrome c heme iron. However, Met80 can be replaced by other endogenous or exogenous ligands forming different non‐native states. The identification of specific ultraviolet–visible absorption and resonance Raman marker bands for each non‐native species has enabled a better insight to be gained into protein unfolding and apoptosis.